The dtxR Gene: A New Alternative Marker to Identify Corynebacterium ulcerans and Corynebacterium pseudotuberculosis by PCR Assay - Sunarno Sunarno; Nyoman Fitri; Nelly Puspandari; Kambang Sariadji (The Indonesian Biomedical Journal, 2018)
BACKGROUND: There are found some studies which reported the successfull of polymerase chain reaction (PCR) assay to identify Corynebacterium ulcerans and Corynebacterium pseudotuberculosis. This study aimed to describe the dtxR gene profile as a new marker for C. ulceran and C. pseudotuberculosis for the PCR assay.METHODS: Ten C. ulcerans and 35 C. pseudotuberculosis DNA sequences data registered in GeneBank was analyzed by bioinformatic tools. PCR primer was designed based on the concerved region and the gene similarity data. On the other hands, reference strains (C. ulcerans NCTC 12077 and Corynebacterium diphtheriae NCTC 3984) and dtxR gene of C. pseudotuberculosis (synthetic gene) were used in the PCR assay optimization for C. ulcerans and C. pseudotuberculosis identification.RESULTS: The study showed that dtxR genes of both C. ulcerans and C. pseudotuberculosis were more conserve than pld gene, moreover dtxR gene was more specific compared to 16S rRNA gene. PCR assay with dtxR gene as a target could identify C. ulcerans and C. pseudotuberculosis accurately without mispriming, misamplification and misidentification.CONCLUSION: dtxR gene could be used as marker to identify C. ulcerans and C. pseudotuberculosis by PCR assay.KEYWORDS: C. pseudotuberculosis, C. ulcerans, dtxR gene, PCR